Impact of changes in sea ice cover on the wave climate of semi-enclosed, seasonally ice-covered water bodies at temperate latitudes: a case study in the Gulf of Riga - Fatemeh Najafzadeh; Tarmo Soomere (Estonian Journal of Earth Sciences, 2024)
We analyse potential changes in the average and cumulative properties of wind waves owing to the loss of sea ice in regions that are currently seasonally ice-covered. The focus is on the Gulf of Riga, located in the eastern Baltic Sea at higher temperate latitudes. This water body is almost isolated from the rest of the Baltic Sea in terms of wave and ice fields. We compare the statistical properties of wave time series from a hypothetical ice-free wave simulation for the period 1990â2021 with truncated ones in which waves are ignored during the ice season. These simulations are made using the SWAN model with a spatial resolution of about 1 nautical mile for the whole gulf and down to 300 m in its nearshore, and forced with ERA5 wind data. The presence of seasonal ice cover insignificantly impacts the formal average wave properties, but the total loss of sea ice will significantly increase the levels of annual cumulative wave energy and its flux, and will thus add considerable energy to coastal processes in this water body.